A taxing incentive? a comparison of retirement saving using discretionary investment and Regulation 28 in a Life-Cycle Model - Burgers, Thomas (Department of Finance and Tax, 2016)
The purpose of this study is to investigate whether the limitations, imposed by Regulation 28 of the Pension Funds Act, encourage optimal asset allocation and reduce investment risk for retirement savings when contrasted to discretionary investment. A quantitative risk and return analysis was performed using available data for Regulation 28 compliant funds and the Johannesburg Stock Exchange indices. The analysis considers two hypothetical investors who are identical in all regards other than their choice of investments. The model used a 40 year working and saving horizon, whereby the investors contribute a portion of their income to a retirement savings vehicle of their choice. The savings in these vehicles accumulate and earn real returns until retirement. The analysis uses a life-cycle model (Modigliani & Brumberg,1954) which accumulates capital to the retirement date and retirement withdrawals that result in zero capital at the date of death, which is assumed to be 20 years postretirement. The model is used to analyse the differential return required in order to make investors indifferent between investing in a regulated product which is incentivised through tax credits. The findings indicate that Regulation 28 is effective in reducing the investment risk of retirement savings, however may also force the investor to sacrifice wealth. Discretionary investment may be preferential to an investor depending on the tax bracket the investor is in. Further, the complex calculations required to smooth consumption over the life cycle may contain too many variables for the ordinary individual to compute. This study is limited by assumptions regarding changes in future tax legislation, the time frame of investment returns for discretionary investment and retirement funds, inflation, investor career length and life expectancy.